Evaluation of endometriosis-associated pain and influence of conventional treatment: A systematic review - De Marqui, Alessandra Bernadete Trovó [UNESP] (FapUNIFESP (SciELO), 2015)
Endometriosis is a chronic gynecological disease characterized by sustained painful symptoms that are responsible for a decline in the quality of life of sufferers. Conventional treatment includes surgical and pharmacological therapy aiming at reducing painful symptoms. This study aimed to evaluate pain levels in women with endometriosis, focusing on the influence of conventional treatment in controlling this variable. To do so, a literature search was conducted in the Medline/Pubmed databases, with 119 scientific articles found. After applying the inclusion and exclusion criteria, 27 were selected for reading and elaboration of this review. Thus, 9 studies evaluated the contribution of surgery, 17 the use of drugs to reduce pain levels in patients with endometriosis and one assessed surgical and medical treatment. The main results of these searches are presented and discussed in this revision. Surgery and the use of drugs provided reduced pain scores in patients with endometriosis but nevertheless exhibit disadvantages, such as risk of recurrence and side effects, respectively. Treatment of endometriosis is, therefore, a challenge for gynecologists and patients, as they must select the best therapeutic approach for this disease. However, improved quality of life in these patients has been obtained with the use of conventional treatment.
Keywords: Endometriosis; Pelvic pain; Quality of life; Therapeutics